Evolutionary conservation of drug action on lipoprotein metabolism-related targetss⃞ - Abdelmadjid K. Hihi; Marie-Claude Beauchamp; Robyn Branicky; Annick Desjardins; Isabel Casanova; Marie-Pierre Guimond; Melissa Carroll; Melanie Ethier; Irenej Kianicka; Kevin McBride; Siegfried Hekimi (Journal of Lipid Research, 2008)
Genetic analysis has shown that the slower than normal rhythmic defecation behavior of the clk-1 mutants of Caenorhabditis elegans is the result of altered lipoprotein metabolism. We show here that this phenotype can be suppressed by drugs that affect lipoprotein metabolism, including drugs that affect HMG-CoA reductase activity, reverse cholesterol transport, or HDL levels. These pharmacological effects are highly specific, as these drugs affect defecation only in clk-1 mutants and not in the wild-type and do not affect other behaviors of the mutants. Furthermore, drugs that affect processes not directly related to lipid metabolism show no or minimal activity. Based on these findings, we carried out a compound screen that identified 190 novel molecules that are active on clk-1 mutants, 15 of which also specifically decrease the secretion of apolipoprotein B (apoB) from HepG2 hepatoma cells. The other 175 compounds are potentially active on lipid-related processes that cannot be targeted in cell culture. One compound, CHGN005, was tested and found to be active at reducing apoB secretion in intestinal Caco-2 cells as well as in HepG2 cells. This compound was also tested in a mouse model of dyslipidemia and found to decrease plasma cholesterol and triglyceride levels. Thus, target processes for pharmacological intervention on lipoprotein synthesis, transport, and metabolism are conserved between nematodes and vertebrates, which allows the use of C. elegans for drug discovery.